The comparison of dual wavelength fiber laser spectrum in SMF and HNLF by utilizing laser diode - Jamaludin, J.; Zakaria, Z.; Awang, N. A.; Zulkifli, M. Z. (Asian Research Publishing Network (ARPN), 2016)
A dual-wavelength erbium-doped fiber (EDF) fiber ring laser in single mode fiber and highly nonlinear fiber is demonstrated and both optical spectrums are compared at 400 mA of Laser Diode (LD) output. The fiber ring laser cavity incorporated sagnac loop had been applied for the laser to lase two wavelengths simultaneously due to high birefringent in polarizaton-maintaining fiber (PMF). Experimental results show that, owing to the contributions of two degenerate fourwave mixings (FWM) in the HNLF and the dual-wavelength proposed fiber laser is quite stable with small fluctuation power in 1.93 dB within 24 minutes in HNLF.